Optimization of Parameters Using Response Surface Methodology to Develop a Novel Kefir-Like Functional Beverage from Cheese Whey Enriched with Myrtle Juice - Sana M’hir; Asma Mejri; Hajer Atrous; Lamia Ayed (Journal of Chemistry)
Whey, liquid wastewater from cheese production, is one of the sources of dietary protein and lactose that are still largely unused for human consumption. It is only in recent years that it has aroused the interest of industries and sought as a valuable raw material and thus represents an opportunity for the manufacture of new products. The manufacture of fermented whey drink requires the mixing of whey with fruit juice or an aromatic plant to improve its organoleptic properties and acceptability. Myrtle, an aromatic medicinal plant, known for its health benefits is not well exploited for making dairy products. This is the first report on the development of kefir-myrtle beverage. Three factors were optimized (whey permeates (%), myrtle’s juice (%), and kefir grains as inoculum (%)) using a central composite design with response surface methodology. The analyses showed that the number of lactic acid bacteria (LAB) and yeast cells varied from 5.4 to 9.2 log10 CFU/mL and from 4.3 to 6.2 log10 CFU/mL, respectively. A decrease in pH and an increase in the total polyphenol content and antioxidant activity were observed. The analysis of variance indicated the goodness of fit of the model with R2 from 0.827 to 0.966. The absolute average deviation values of each model were low and ranged from 1.61% to 4.23%. The optimized fermented kefir whey beverage accomplished an overall acceptability of 5.41 (1 to 9 preference scale) and a high number of LAB cells (8.53 log10 CFU/mL). The viability of LAB and yeast cell was maintained at 7.61 and 6.19 log10 CFU/mL, respectively, after 14 days of storage.